World War Z [videorecording (DVD)] - Forster, Marc, 1969-; Pitt, Brad, 1963-; Brooks, Max; Enos, Mireille, 1975-; Dale, James Badge, 1978- (Paramount, 2013)
Gerry Lane travels the globe in an effort to eliminate the zombie pandemic that is endangering the existence of humanity.